Islam Tengger: Ihwal, Persebaran, Tradisi dan Transformasi Sosial Keagamaan: Studi Kasus Di Kecamatan Tosari, Pasuruan, Jawa Timur: Islam Tengger: Origins, Distribution, Traditions, and Socio-Religious Transformation: A Case Study in Tosari District, Pasuruan, East Java - Moh. Khusnurridlo (Fenomena, 2002)
The socio-historical development of Islam in Indonesia’s pluralistic Tengger region remains underexplored despite its unique interreligious dynamics. This study addresses the gap by examining the history of Islam’s entry and development, identifying factors that support or hinder its spread, and projecting its prospects in the Tengger community of Tosari, Pasuruan. Using a qualitative case study design, data were collected through in-depth interviews, participant observation, and documentation, then analyzed interpretively. Findings indicate that Islam began spreading around 1910 through trade, with organized da'wah intensifying in the 1920s, led by KH. Ahmad Dahlan. Islamic traditions have been practiced adaptively in Hindu-majority settings, fostering inclusive socio-religious relations rather than conflict. Key propagation channels included education, trade, marriage, and missionary efforts. The study concludes that Islam’s future in Tengger is promising, supported by intergenerational transmission and local pluralism. Recommendations emphasize strengthening religious education and interfaith dialogue to sustain constructive coexistence. Perkembangan sosiohistoris Islam di kawasan Tengger yang pluralistik masih kurang terungkap meskipun dinamika antaragama yang unik. Penelitian ini mengisi kesenjangan tersebut dengan mengkaji sejarah masuk dan berkembangnya Islam, mengidentifikasi faktor pendukung dan penghambat, serta memproyeksikan prospeknya di masyarakat Tengger, Tosari, Pasuruan. Dengan desain studi kasus kualitatif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi, lalu dianalisis secara interpretatif. Temuan menunjukkan Islam mulai menyebar sekitar tahun 1910 melalui jalur perdagangan, dengan dakwah terorganisasi meningkat pada 1920-an yang digerakkan oleh KH. Ahmad Dahlan. Tradisi keislaman dipraktikkan secara adaptif di tengah masyarakat mayoritas Hindu, mendorong hubungan sosial-keagamaan yang inklusif而非 konflik. Jalur utama penyebaran meliputi pendidikan, perdagangan, perkawinan, dan dakwah. Kesimpulannya, masa depan Islam di Tengger prospektif, didukung transmisi antargenerasi dan pluralisme lokal. Rekomendasi mengarah pada penguatan pendidikan agama dan dialog lintas iman untuk keberlanjutan koeksistensi konstruktif.